A Pilot Application and Reliability of JEPQR-A on Preadolescent Greek Students - Glania Τριανταφυλλιά; Antoniou Παναγιώτης; Digelidis Νικόλαος (Inquiries in Physical Education and Sport, 2007)
The purpose of the present study was to apply the JEPQR-A and check its reliability when translated in Greek. Moreover, possible differences on personality characteristics between sexes were explored. Five hundred and fifty three primary school children (289 boys and 264 girls) aged 11-12 years old completed the Junior Eysenck Personality Questionnaire Revised-Abbreviated (JEPQR-A) concerning extraversion, neuroticism, psychotism and lie. The questionnaire was translated into Greek and vise versa by experienced teachers. All subscales had coefficients Cronbach (a>.64) and ICC (ICC>.73) from satisfactory to very good. The internal consistency of every subscale was checked through item analysis and revealed good to high correlations (p<.05 or p<.01). The Manova analysis indicated that boys were more psychotic but less neurotic compared to girls. Since similar surveys have not been performed in Greece and few have been done on personality characteristics of Greek preadolescents, a specification and comparison of their personality characteristics can be made on the results of the present survey. Future surveys on pilot applications of foreign questionnaires are useful be performed in Greece, to explore possible personality differences between sexes.